Về ứng dụng của ngôn ngữ lập trình Mathematica trong xích Maxkov - Long, Nguyễn Việt; Quang, Ung Ngọc (Journal of Computer Science and Cybernetics, 2016)
This paper presents an application of Mathematica Programing to Markov chains.